Prospective study of radiological and functional outcomes of humeral mid-shaft fractures by anterior bridge plating technique - Dey, Joydeep Kumar; Shetty, Sunil H.; Singh, Shikhar Dalbir; Srivastava, Abhilash; Agrawal, Sarang; Modi, Ravi Rajan; Jyoti, Venkatesh; Gehlot, Ojasv (International Journal of Research in Orthopaedics, 2023)
Background: The humerus can be considered the most versatile bone in the human body. Can be successfully approached by a variety of methods for fracture fixation including functional bracing, plating (posterior, lateral, and anterior), and intramedullary nailing (antegrade and retrograde). Notably, many humeral fractures can be successfully managed conservatively due to the wide range of acceptability for reduction. Anterior bridge plating (ABP) which utilizes the minimally invasive approach popularly known as the minimally invasive percutaneous plate osteosynthesis (MIPPO) technique can be said to be the latest entrant in this list. The present study was undertaken to evaluate the efficacy of ABP. Methods: The study was carried out from July 2020 to July 2022 in DR. D. Y. Patil medical college and hospital, Nerul, Navi Mumbai, involving 32 patients who met the selection criteria and were operated at the tertiary care centre. Informed consent was obtained from all the patients for use of their clinical and imaging data. Ethical committee approval was taken. The assessment of the patients was done based on functional and radiological outcomes periodically. Results: Majority of patients belongs to age group 18-25 years (46.87%). Majority of side of injury were found right side (65.62%). In most of the cases, the extent of the displacement of fractures were 2-5 cm (71.87). Conclusions: In conclusion ABP is a very good technique in treating mid-shaft humeral fractures with minimal soft tissue dissection, smaller scars, and early return to overhead activities.